Dynamic and Permanent Gratings in Suspensions of Absorbing Nanocrystals in Organic Solvent - Kredentser, Sergey; Eremin, Alexey; Davidson, Patrick; Reshetnyak, Victor; Stannarius, Ralf; Reznikov, Yuri (Photonics Letters of Poland, 2015)
<!-- saved from url=(0022)http://internet.e-mail --> Both dynamic and permanent optical gratings were recorded in the suspension of absorbing pigment nanocrystallites in organic solvent. The dynamic gratings were recorded due to the transfer of the nanocrystallites in the temperature gradient induced by light interference pattern, and the permanent gratings were formed due to light-induced adsorption of the nanocrystalites on the surface of the cell substrate. Full Text: PDF References B.Y. Zel'dovich, N. V Tabiryan, "Orientational optical nonlinearity of liquid crystals", Sov. Phys. Uspekhi 28, 1059 (1985). CrossRef K. Thyagarajan, P. Lallemand, "Determination of the thermal diffusion ratio in a binary mixture by forced Rayleigh scattering", Opt. Commun. 26, 54 (1978). CrossRef F. Bloisi, L. Vicari, P. Cavaliere, S. Martellucci, J. Quartieri, P. Mormile, G. Pierattini, A. Felice, "Soret effect in forced Rayleigh scattering", Appl. Phys. B 106, 103 (1987). CrossRef W. Köhler, "Thermodiffusion in polymer solutions as observed by forced Rayleigh scattering", Chem. Phys. 98, 660 (1993). CrossRef J. Zamir Anvari, R. Karimzadeh, N. Mansour, "Thermo-optic properties and nonlinear responses of copper nanoparticles in polysiloxane oil", J. Opt. 12, 035212 (2010). CrossRef N.M. Rouhollah Karimzadeh, "Investigation of the Soret effect in copper nanoparticle colloids by self-phase modulation and Z-scan", J. Mod. Opt. 60, 163 (2013). CrossRef N. Tabiryan, W. Luo, "Soret feedback in thermal diffusion of suspensions", Phys. Rev. E 57, 4431 (1998). CrossRef A. Eremin, R. Stannarius, S. Klein, J. Heuer, R.M. Richardson, "Switching of Electrically Responsive, Light-Sensitive Colloidal Suspensions of Anisotropic Pigment Particles", Adv. Funct. Mater. 21, 556 (2011). CrossRef I.C. Khoo, "Nonlinear optics of liquid crystalline materials", Phys. Rep. 471, 221 (2009). CrossRef H. Löwen, "Anisotropic self-diffusion in colloidal nematic phases", Phys. Rev. E 59, 1989 (1999). CrossRef S. Kredentser, A. Eremin, P. Davidson, V. Reshetnyak, R. Stannarius,Y. Reznikov, submitted to Eur. Phys. J. E (2015). CrossRef